Implant prosthesis and preparation method thereof
By combining the design of metal support and polymer material exobody, the problem of low overall performance of existing femoral head implants is solved, and higher durability and biocompatibility are achieved, reducing the risk of complications.
Patent Information
- Application Number
- CN202411093948.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The comprehensive performance of existing femoral head implants is low, and there are problems such as insufficient mechanical strength, high friction coefficient, high brittleness and stress masking effects.
Using an implant prosthesis design that combines metal support and polymer material exterior bodies, the metal support provides mechanical strength, polymer material exterior bodies improve biocompatibility and friction characteristics, and achieves a firm bond through a unique mechanical connection structure.
It improves the durability of the implant, reduces the risk of fracture and wear, improves the mechanical matching with bone tissue, alleviates the stress shading effect, and promotes the remodeling of surrounding bone tissue.
Smart Images

Figure CN118750236B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to an implant prosthesis and a preparation method thereof. Background Art
[0002] Femoral head implants are medical devices used to replace damaged or diseased femoral heads and are widely used in total hip replacement surgery. Femoral head implants are designed to mimic the shape and function of the natural femoral head and include a spherical portion to fit with the acetabular prosthesis or natural acetabular socket joint and a tapered portion to connect with the femoral stem. This design allows patients to restore normal range of motion and weight-bearing capacity of the hip joint after surgery.
[0003] Femoral head implants in the prior art usually adopt an all-metal structure or an all-ceramic structure. Although the all-metal structure has excellent mechanical strength, the friction coefficient between it and the acetabular prosthesis is high, which may lead to increased wear, generate a large amount of wear debris, and induce inflammatory response and bone dissolution in the surrounding tissues. Although the all-ceramic structure has good biocompatibility and wear resistance, it has the problem of high brittleness and the risk of fracture. In addition, the elastic modulus of these two structures and bone tissue is quite different, which may lead to stress shielding effect, affecting the long-term fixation effect and the remodeling of the surrounding bone tissue.
[0004] Currently, the limitations of existing femoral head implants have prompted researchers to seek new material combinations and structural designs to improve the overall performance of femoral head implants. Summary of the invention
[0005] The main purpose of the present invention is to solve the technical problem that the comprehensive performance of the femoral head implant in the prior art is low.
[0006] The first aspect of the present invention provides an implant prosthesis, which includes a metal support and an outer body, the metal support includes an annular wall, the material of the annular wall is a biocompatible metal or its alloy, and a mechanical connection structure is provided on the annular wall, and the mechanical connection structure includes a first through hole penetrating the annular wall and / or a groove body recessed on the peripheral wall of the annular wall; the outer body includes a spherical portion, a conical portion and a solidifying portion, the spherical portion is connected to the outer peripheral wall of the annular wall and is used for implanting into the acetabulum, the conical portion is connected to the inner peripheral wall of the annular wall and forms a conical groove for connecting with the femoral stem, the solidifying portion is arranged in the mechanical connection structure, the spherical portion, the conical portion and the solidifying portion are integrally formed, and the materials of the spherical portion, the conical portion and the solidifying portion are all biocompatible polymer materials.
[0007] Optionally, the mechanical connection structure includes the first via hole;
[0008] There are multiple first vias, which are spaced apart in the circumferential direction of the annular wall. There are multiple solidified parts, which are the same as and correspond to the first vias, and the solidified parts fill the corresponding first vias.
[0009] Optionally, the mechanical connection structure includes a slot body;
[0010] There are multiple groove bodies, and the multiple groove bodies are all arranged on the outer peripheral wall of the annular wall and are spaced apart in the circumferential direction of the annular wall. There are multiple solidification parts, and the number of the multiple solidification parts is the same as the number of the multiple groove bodies and corresponds one to one. The solidification parts fill the corresponding groove body settings.
[0011] Optionally, the metal support further includes a spherical cap wall, which is connected to the end of the annular wall away from the notch of the tapered groove and protrudes in a direction away from the notch of the tapered groove.
[0012] Optionally, the spherical crown wall is penetrated by a second through hole, the outer body includes a connecting portion, the connecting portion fills the second through hole, the connecting portion is integrally formed with the spherical portion and the conical portion, and the material of the connecting portion is a biocompatible polymer material.
[0013] A second aspect of the present invention provides a method for preparing an implant prosthesis, comprising:
[0014] Providing a metal support with a preset geometry and surface properties;
[0015] The biocompatible polymer material is subjected to supercritical fluid-assisted spray treatment, and the particles obtained after the treatment are electrostatically collected and characterized to obtain nanoparticles with uniform particle size distribution;
[0016] Placing the metal support in a suspension containing the nanoparticles and performing a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure;
[0017] Performing femtosecond laser microstructuring on the surface of the initial composite structure to obtain a composite structure having a preset surface microstructure;
[0018] A multi-stage gradient heat treatment is performed on a composite structure with a preset surface microstructure, and a plasma chemical vapor deposition treatment is performed on the composite structure after the heat treatment to obtain an implant prosthesis with a preset shape.
[0019] Optionally, the preparation process of the metal support member includes:
[0020] Selective laser melting of biocompatible metal powder was performed to obtain a metal support prototype;
[0021] Performing hot isostatic pressing on the metal support prototype to obtain a densified metal support;
[0022] Performing surface roughening treatment on the densified metal support to obtain a metal support with a microscopic rough structure;
[0023] Performing X-ray computed tomography on the metal support having the microscopic rough structure to obtain three-dimensional structural data of the metal support;
[0024] Performing surface microstructure modification on the metal support according to the three-dimensional structure data to obtain a metal support with a preset surface morphology;
[0025] The metal support member with a preset surface morphology is subjected to plasma surface activation treatment to obtain a metal support member with a preset geometric structure and surface characteristics.
[0026] Optionally, the biocompatible polymer material is subjected to supercritical fluid-assisted spray treatment, and the particles obtained after the treatment are electrostatically collected and characterized to obtain nanoparticles with uniform particle size distribution, including:
[0027] The biocompatible polymer material and supercritical carbon dioxide are mixed under high pressure to obtain a uniform solution;
[0028] Performing high-pressure spraying on the uniform solution to obtain preliminarily formed nanoparticles;
[0029] treating the initially formed nanoparticles with an ultrasonic field to obtain nanoparticles with improved dispersion;
[0030] Performing electrostatic field collection treatment on the nanoparticles with improved dispersion to obtain a preliminary collected nanoparticle sample;
[0031] Performing dynamic light scattering analysis on the initially collected nanoparticle samples to obtain particle size distribution data;
[0032] The nanoparticle sample is centrifuged and classified according to the particle size distribution data to obtain nanoparticles with uniform particle size distribution.
[0033] Optionally, placing the metal support in a suspension containing the nanoparticles and performing a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure comprises:
[0034] Performing a suspension preparation process on the nanoparticles to obtain a working suspension having a preset electrophoretic property;
[0035] Placing the metal support on a rotating bracket and immersing the metal support in the working suspension, applying an electric field and performing acoustic wave excitation treatment on the metal support to obtain a preliminary deposition structure;
[0036] Performing real-time monitoring and parameter adjustment processing on the preliminary deposition structure to obtain a staged deposition structure with uniform thickness;
[0037] Performing surface activation and position adjustment treatment on the staged deposition structure to obtain an intermediate deposition structure;
[0038] Repeating the above-mentioned electrophoretic deposition, monitoring and adjustment, and surface treatment steps on the intermediate deposition structure to obtain a multilayer deposition structure;
[0039] The multilayer deposition structure is subjected to final surface treatment to obtain an initial composite structure.
[0040] Optionally, the real-time monitoring and parameter adjustment processing of the preliminary deposition structure to obtain a staged deposition structure with uniform thickness includes:
[0041] Conduct multi-dimensional measurement and analysis of the preliminary sedimentary structure to obtain sedimentary layer characteristic data;
[0042] According to the characteristic data of the sediment layer, the electric field and the acoustic field are coupled and optimized to obtain the electric-acoustic composite field;
[0043] Performing spatiotemporal modulation processing on the electro-acoustic composite field to obtain a dynamic deposition field;
[0044] Performing multi-scale simulation processing on the nanoparticle deposition process according to the dynamic deposition field to obtain a deposition parameter prediction model;
[0045] Performing machine learning training on the deposition parameter prediction model to obtain an intelligent deposition control model;
[0046] According to the intelligent deposition control model, the deposition parameters are adjusted and optimized in real time to obtain dynamically optimized deposition parameters;
[0047] The dynamically optimized deposition parameters are used to perform closed-loop controlled deposition processing on the preliminary deposition structure to obtain a staged deposition structure with uniform thickness.
[0048] The implant prosthesis proposed by the present invention effectively solves the problems existing in the prior art by innovatively combining a metal support and a polymer outer body. The metal support provides the necessary mechanical strength and overcomes the defect of easy fracture of the all-ceramic structure; while the polymer outer body significantly improves the biocompatibility and friction characteristics, and solves the problem of high friction coefficient and easy generation of wear debris in the all-metal structure. In particular, by designing a unique mechanical connection structure (including a first via and / or a slot body) on the annular wall of the metal support, and filling the solidified part of the polymer material therein, the metal support and the polymer outer body are firmly combined, ensuring the integrity and functionality of the overall structure. This composite structure can not only reduce wear and reduce the risk of fracture, but also better match the mechanical properties of bone tissue and effectively alleviate the stress shielding effect. The integrated design of the spherical part and the conical part further enhances the structural stability of the implant. In addition, the use of polymer materials makes the elastic modulus of the implant closer to that of bone tissue, which is conducive to improving the long-term fixation effect and promoting the remodeling of the surrounding bone tissue. Therefore, the implant prosthesis of the present invention has significant advantages in improving durability, reducing the risk of complications and improving the quality of life of patients. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0050] Figure 1 It is a schematic diagram of the structure of the implant prosthesis and the femoral stem of the present invention;
[0051] Figure 2 It is a schematic diagram of the structure of the implant prosthesis of the present invention cooperating with the acetabular prosthesis;
[0052] Figure 3 is a cross-sectional schematic diagram of an implant prosthesis of the present invention;
[0053] Figure 4 It is an exploded schematic diagram of the implant prosthesis of the present invention;
[0054] Figure 5 It is a structural schematic diagram of another embodiment of a metal support;
[0055] Figure 6 The present invention is a flowchart of an embodiment of a method for preparing an implant prosthesis.
[0056] Description of Figure Numbers:
[0057] 1. Metal support; 11. Annular wall; 12. Mechanical connection structure; 121. First through hole; 122. Groove body; 13. Spherical cap wall; 131. Second through hole; 2. Outer body; 21. Spherical part; 22. Conical part; 221. Conical groove; 23. Solidification part; 24. Connection part; 100. Acetabular socket; 200. Femoral stem.
[0058] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0061] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, "and / or" in the full text includes three solutions. Taking A and / or B as an example, it includes technical solution A, technical solution B, and technical solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, which must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0062] An embodiment of the present application provides an implant prosthesis. Figures 1 to 5The implant prosthesis comprises a metal support 1 and an outer body 2, wherein the metal support 1 comprises an annular wall 11, wherein the material of the annular wall 11 is a biocompatible metal or its alloy, wherein a mechanical connection structure 12 is provided on the annular wall 11, wherein the mechanical connection structure 12 comprises a first through hole 121 penetrating the annular wall 11 and / or a groove 122 recessed on the peripheral wall of the annular wall 11; wherein the outer body 2 comprises a spherical portion 21, a conical portion 22 and a solidifying portion 23, wherein the spherical portion 21 It is connected to the outer peripheral wall of the annular wall 11 and is used for implanting the acetabulum 100, the conical portion 22 is connected to the inner peripheral wall of the annular wall 11 and forms a conical groove 221 for connecting with the femoral stem 200, the solidifying portion 23 is arranged in the mechanical connection structure 12, the spherical portion 21, the conical portion 22 and the solidifying portion 23 are integrally formed, and the materials of the spherical portion 21, the conical portion 22 and the solidifying portion 23 are all biocompatible polymer materials.
[0063] Specifically, the annular wall 11 is a three-dimensional structure, and its cross section can be circular, elliptical or other closed curve shapes. The material of the annular wall 11 is limited to biocompatible metals or their alloys, specifically metals such as titanium, cobalt, chromium, or their alloys, such as titanium alloys, cobalt-chromium alloys, etc. These materials have good biocompatibility and mechanical strength, and are suitable for long-term implantation in the human body.
[0064] The first through hole 121 is a hole that completely penetrates the annular wall 11. The cross section of the peripheral wall of the first through hole 121 can be circular, square, elliptical or other shapes. The groove body 122 is a recessed structure on the surface of the annular wall 11, which can be a groove of various shapes such as U-shaped, V-shaped, semicircular, etc. The purpose of these structures is to increase the bonding area and mechanical bite force between the metal support 1 and the outer body 2, and improve the stability of the overall structure.
[0065] The spherical portion 21 is connected to the outer peripheral wall of the annular wall 11 and is used to implant the acetabular fossa 100. Its shape should be similar to that of the natural femoral head, usually a smooth spherical surface to ensure good fit and sliding with the acetabular prosthesis or the natural acetabular fossa 100. The conical portion 22 is connected to the inner peripheral wall of the annular wall 11 to form a conical groove 221 for connecting with the femoral stem 200. This conical groove 221 is an inwardly recessed conical space, and its angle and size should match those of the standard femoral stem 200 to ensure a stable connection. The solidified portion 23 is filled in the mechanical connection structure 12, that is, in the first through hole 121 and / or the slot body 122, to play a role in firmly connecting the spherical portion 21, the conical portion 22 and the metal support 1.
[0066] The spherical part 21, the conical part 22 and the curing part 23 are integrally formed, and their materials are all biocompatible polymer materials. Such polymer materials can be polyetheretherketone (PEEK), polyurethane, ultra-high molecular weight polyethylene (UHMWPE), etc., all of which have good biocompatibility, wear resistance and mechanical properties. Integral molding means that the three parts are formed simultaneously during the manufacturing process without seams or connection points, which can improve the strength and durability of the overall structure.
[0067] It can be understood that the implant prosthesis of the present invention cleverly combines the high strength of the metal support 1 with the good biocompatibility and low friction coefficient of the polymer material. The metal support 1 provides the necessary mechanical strength and solves the problem of easy fracture of the all-ceramic structure; while the polymer material outer body 2 significantly improves the biocompatibility and friction characteristics, overcoming the shortcomings of the all-metal structure with high friction coefficient and easy generation of wear debris. Through the unique design of the mechanical connection structure 12, the metal support 1 and the polymer outer body 2 are firmly combined to ensure the integrity and functionality of the overall structure. This composite structure can not only reduce wear and reduce the risk of fracture, but also better match the mechanical properties of bone tissue and effectively alleviate the stress shielding effect. The use of polymer materials makes the elastic modulus of the implant closer to that of bone tissue, which is conducive to improving the long-term fixation effect and promoting the remodeling of the surrounding bone tissue. Therefore, this design has significant advantages in improving durability, reducing the risk of complications and improving the quality of life of patients.
[0068] Specifically, the outer surface roughness Ra of the spherical part 21 is not higher than 0.5 microns, and the roundness is not higher than 0.1 microns. The low surface roughness and high roundness accuracy of the spherical part 21 can significantly reduce the friction and wear between the acetabular prosthesis and the acetabular prosthesis, prolong the service life of the implant, and reduce the risk of generating wear debris, thereby reducing the inflammatory response of the surrounding tissue and the possibility of bone dissolution.
[0069] The design of the tapered groove 221 adopts a Morse taper with an angle between 2.85° and 6.36°. The tapered groove 221 designed with a Morse taper can ensure a tight and stable connection with the femoral stem 200, effectively prevent micro-movement, and improve the stability and reliability of the overall structure. This precise design not only improves the mechanical properties and durability of the implant, but also improves the patient's activity comfort and reduces the risk of postoperative complications, thereby significantly improving the patient's quality of life and satisfaction.
[0070] Optionally, the mechanical connection structure 12 includes the first via hole 121;
[0071] There are multiple first vias 121, which are spaced apart in the circumferential direction of the annular wall 11. There are multiple solidifying parts 23, which are the same as and correspond to the multiple first vias 121. The solidifying parts 23 fill the corresponding first vias 121.
[0072] Specifically, the plurality of first through holes 121 may be evenly distributed in the circumferential direction of the annular wall 11 , or may be irregularly distributed according to specific requirements.
[0073] Through the multiple first through holes 121 and the corresponding solidification parts 23, the contact area and mechanical bite force between the metal support 1 and the outer body 2 are significantly increased. This structure not only improves the structural integrity and stability of the overall implant prosthesis, but also better disperses stress and reduces local stress concentration. The provision of multiple solidification parts 23 also increases the torsion resistance of the entire structure, allowing the implant to perform better when subjected to complex loads. In addition, this design also increases the interface area between the metal support 1 and the polymer material outer body 2, which is beneficial to improving the heat conduction efficiency and reducing the risk of local overheating.
[0074] Optionally, the mechanical connection structure 12 includes a slot 122;
[0075] There are multiple groove bodies 122, and the multiple groove bodies 122 are all arranged on the outer wall of the annular wall 11 and are spaced apart in the circumferential direction of the annular wall 11. There are multiple solidification parts 23, and the number of the multiple solidification parts 23 is the same as the number of the multiple groove bodies 122 and corresponds one to one. The solidification parts 23 fill the corresponding groove bodies 122.
[0076] It is not difficult to understand that by providing a plurality of grooves 122 on the outer peripheral wall of the annular wall 11 and filling them with polymer materials, the contact area and mechanical bite force between the metal support 1 and the outer body 2 are significantly increased. The presence of the grooves 122 increases the interface area between the metal support 1 and the polymer outer body 2, which is conducive to the uniform distribution of stress and reduces local stress concentration. The circumferential distribution of multiple grooves 122 improves the torsion resistance of the entire structure, making the implant perform better when subjected to complex loads. In addition, this design may also provide better thermal conductivity, which helps reduce the risk of local overheating.
[0077] Optionally, the metal support 1 further includes a spherical cap wall 13 , which is connected to the end of the annular wall 11 away from the notch of the tapered groove 221 and protrudes in a direction away from the notch of the tapered groove 221 .
[0078] It is not difficult to understand that the addition of the spherical cap wall 13 increases the overall strength and stability of the metal support 1. The convex shape provides additional support area, which can better disperse the load from the hip joint. At the same time, this structure also increases the contact area between the metal support 1 and the polymer material outer body 2, further enhancing the bonding strength between the two. The presence of the spherical cap wall 13 can also improve stress distribution and reduce local stress concentration, thereby reducing the risk of material fatigue and failure. In addition, this design may better simulate the morphology of the natural femoral head and help optimize the biomechanical properties of the implant.
[0079] Optionally, the spherical crown wall 13 is penetrated by a second through hole 131, and the outer body 2 includes a connecting portion 24, which fills the second through hole 131, and the connecting portion 24 is integrally formed with the spherical portion 21 and the conical portion 22, and the material of the connecting portion 24 is a biocompatible polymer material.
[0080] Specifically, the material of the connecting portion 24 is the same as that of the spherical portion 21 and the conical portion 22, which are both biocompatible polymer materials. Such materials may be polyetheretherketone (PEEK), polyurethane, ultra-high molecular weight polyethylene (UHMWPE), etc., which have good biocompatibility, wear resistance and mechanical properties.
[0081] It is not difficult to understand that by providing a second through hole 131 on the spherical crown wall 13 and filling it with a polymer material, the contact area and mechanical bite force between the metal support 1 and the outer body 2 are further increased. The presence of the connecting portion 24 creates a polymer material network that runs through the entire implant prosthesis, significantly enhancing the integrity and stability of the overall structure. This design not only improves the bonding strength between the metal support 1 and the outer body 2, but also improves the stress distribution of the entire structure and reduces the risk of local stress concentration. The one-piece design eliminates potential weaknesses and stress concentration areas, and improves the durability of the overall structure. In addition, this design may also provide better thermal conductivity, help to evenly disperse heat, and reduce the risk of local overheating.
[0082] Another embodiment of the present application further provides a method for preparing an implant prosthesis, which is used to prepare the implant prosthesis provided in the above embodiment. Figure 6 A flow chart of a method for preparing an implant prosthesis provided in one embodiment of the present application.
[0083] See also Figure 6 , providing metal supports with preset geometric structures and surface properties.
[0084] In one embodiment of the present invention, the preparation process of the metal support part with preset geometric structure and surface characteristics includes: performing selective laser melting treatment on biocompatible metal powder to obtain a metal support part prototype; performing hot isostatic pressing treatment on the metal support part prototype to obtain a densified metal support part; performing surface roughening treatment on the densified metal support part to obtain a metal support part with a microscopic rough structure; performing X-ray computed tomography detection on the metal support part with a microscopic rough structure to obtain three-dimensional structural data of the metal support part; performing surface microstructure modification on the metal support part according to the three-dimensional structural data to obtain a metal support part with a preset surface morphology; performing plasma surface activation treatment on the metal support part with a preset surface morphology to obtain a metal support part with a preset geometric structure and surface characteristics.
[0085] Specifically, this embodiment uses a high-power laser to melt and solidify metal powder layer by layer to construct a metal support prototype. For example, titanium alloy powder with a particle size range of 20-50 microns is used. Under an argon protective atmosphere, a 200-400 watt fiber laser is used with a scanning speed of 500-1000 mm / s and a layer thickness of 30-50 microns to construct a complex three-dimensional structure layer by layer. This method can accurately manufacture metal supports with complex internal structures, such as mechanical connection structures such as the first via hole and the slot body on the annular wall.
[0086] Next, the metal support prototype is subjected to hot isostatic pressing, a step that can significantly improve the density of the metal support. In this process, the metal support prototype is placed in an autoclave, filled with high-purity argon, heated to 900-1200°C, and the pressure reaches 100-200MPa for 4-6 hours. This treatment method can effectively eliminate the micropores and internal defects that may be generated during the selective laser melting process, thereby obtaining a densified metal support. The densification treatment significantly improves the mechanical properties of the metal support, including strength, toughness and fatigue life.
[0087] Subsequently, the densified metal support is subjected to surface roughening treatment to obtain a metal support with a microscopic rough structure. This step can be performed by sandblasting technology, using aluminum oxide sand particles with a particle size of 100-200 microns, sandblasting at a pressure of 0.4-0.6 MPa, and the treatment time is 5-10 minutes. The surface roughening treatment increases the specific surface area and microstructural complexity of the surface of the metal support, which is conducive to the subsequent adhesion and mechanical locking of the polymer material, thereby enhancing the bonding strength between the metal support and the external body.
[0088] In order to accurately evaluate the internal structure and surface morphology of metal supports, it is necessary to perform X-ray computed tomography on metal supports with microscopic rough structures. Using high-resolution industrial CT equipment, the X-ray source voltage is set to 120-150kV, the current is 100-150μA, 1000-1500 projections are collected, and the reconstructed voxel size is 10-20 microns. Through this non-destructive testing method, detailed three-dimensional structural data of metal supports can be obtained, including information such as internal structure, surface morphology and dimensional accuracy.
[0089] Based on the obtained three-dimensional structure data, the surface microstructure of the metal support is modified to obtain a metal support with a preset surface morphology. This step can be performed using femtosecond laser processing technology, using a femtosecond laser with a wavelength of 800nm, a pulse width of 100fs, and a power density of - W / , with a scanning speed of 10-100mm / s, fine microstructures such as microgrooves, micropores or specific surface patterns are produced on the surface of the metal support. This surface microstructure modification can not only further enhance the bonding strength between the metal support and the polymer material outer body, but also optimize the interaction between the implant and the biological tissue.
[0090] Finally, the metal support with a preset surface morphology is subjected to plasma surface activation treatment to obtain a metal support with a preset geometric structure and surface characteristics. This step uses oxygen plasma, with a power of 100-200W at a pressure of 50-100Pa and a treatment time of 5-10 minutes. Plasma treatment can clean the metal surface, remove organic pollutants, and form active functional groups on the surface to increase surface energy and hydrophilicity. This treatment not only enhances the binding of the metal support with the polymer material, but also improves its biocompatibility.
[0091] Please continue reading Figure 6 , biocompatible polymer materials are subjected to supercritical fluid-assisted spray treatment, and the particles obtained after the treatment are electrostatically collected and characterized and analyzed to obtain nanoparticles with uniform particle size distribution.
[0092] In one embodiment of the present invention, the biocompatible polymer material is subjected to supercritical fluid-assisted spray treatment, and the particles obtained after the treatment are subjected to electrostatic collection and characterization analysis to obtain nanoparticles with uniform particle size distribution, including: high-pressure mixing treatment of the biocompatible polymer material and supercritical carbon dioxide to obtain a uniform solution; high-pressure spray treatment of the uniform solution to obtain initially formed nanoparticles; ultrasonic field treatment of the initially formed nanoparticles to obtain nanoparticles with improved dispersion; electrostatic field collection treatment of the nanoparticles with improved dispersion to obtain initially collected nanoparticle samples; dynamic light scattering analysis of the initially collected nanoparticle samples to obtain particle size distribution data; and centrifugal classification treatment of the nanoparticle samples according to the particle size distribution data to obtain nanoparticles with uniform particle size distribution.
[0093] Specifically, taking polyetheretherketone (PEEK) as an example, PEEK particles are placed in a high-pressure reactor, and supercritical carbon dioxide is introduced at the same time (selecting supercritical carbon dioxide as a solvent has the following advantages: first, supercritical carbon dioxide has a low critical point (31.1°C, 7.38MPa), which is easy to operate; second, it is an environmentally friendly solvent, non-toxic and harmless, and easy to remove; third, supercritical carbon dioxide has low surface tension and high diffusion coefficient, which is conducive to uniformly dissolving polymer materials and forming fine particles; finally, the use of supercritical carbon dioxide can avoid the problem of organic solvent residues and improve the purity and biocompatibility of the product). The temperature and pressure of supercritical carbon dioxide are controlled at 40-60°C and 15-25MPa, respectively. Under this condition, carbon dioxide has both high diffusivity of gas and solubility of liquid. Through continuous stirring and heating, PEEK gradually dissolves in supercritical carbon dioxide to form a uniform solution. This method not only avoids the use of organic solvents and reduces environmental pollution, but also can achieve the dissolution of polymer materials at a lower temperature, effectively preventing thermal degradation of materials.
[0094] Next, the obtained uniform solution is subjected to high-pressure spraying. The solution is sprayed into a low-pressure chamber at high speed through a nozzle (aperture 50-150μm). The temperature of the low-pressure chamber is maintained at 30-50°C and the pressure is 0.1-0.5MPa. When the high-pressure solution enters the low-pressure environment, the supercritical carbon dioxide expands and vaporizes rapidly, causing the solution to atomize instantly and form tiny droplets. During the flight of these droplets, the solvent (supercritical carbon dioxide) evaporates rapidly, leaving solidified PEEK nanoparticles. This high-pressure spray method can produce preliminary nanoparticles with uniform particle size and regular morphology, and the entire process does not require the use of organic solvents, which is environmentally friendly.
[0095] In order to further improve the dispersion of nanoparticles, the initially formed nanoparticles are treated with an ultrasonic field. The particles are suspended in deionized water and ultrasonically dispersed using an ultrasonic treatment device with a power of 500-1000W and a frequency of 20-60kHz. When ultrasound propagates in a liquid, a cavitation effect is produced, forming a large number of tiny bubbles. The rupture of these bubbles will produce a strong impact force, effectively breaking up the agglomeration of particles and improving dispersion. The treatment time is usually controlled at 15-30 minutes, during which the dispersion effect can be optimized by adjusting the ultrasonic power and pulse mode. Ultrasonic treatment can not only improve the dispersion of nanoparticles, but also regulate the morphology and size distribution of particles to a certain extent.
[0096] Subsequently, the nanoparticles with improved dispersion are collected by electrostatic field. The nanoparticle suspension is atomized through a charged nozzle, and a high voltage electric field of 10-30kV is applied between the nozzle and the collection plate. The charged nanoparticles move toward the collection plate under the action of the electric field and are deposited on the collection plate. This electrostatic collection method can effectively separate and collect nanoparticles, reduce particle agglomeration, and can also control the deposition density and uniformity of the particles by adjusting the electric field strength and collection distance.
[0097] In order to accurately evaluate the size distribution of nanoparticles, dynamic light scattering analysis is performed on the initially collected nanoparticle samples. The nanoparticles are dispersed in an appropriate solvent and measured using a dynamic light scattering instrument. This technology is based on the principle of Brownian motion and calculates the hydrodynamic diameter of the particles by analyzing the time-correlated function of the scattered light intensity. Through repeated measurements and data fitting, accurate particle size distribution data can be obtained, including key parameters such as average particle size and polydispersity index.
[0098] Finally, the nanoparticle samples are centrifuged and graded according to the particle size distribution data. The nanoparticle suspension is placed in a centrifuge tube and graded using a high-speed centrifuge. By adjusting the centrifugal speed (usually 5000-20000 rpm) and the centrifugal time (5-30 minutes), particles of different particle size ranges can be separated according to Stokes' law. By sampling from top to bottom, nanoparticles with a more uniform particle size distribution can be obtained. This centrifugal classification method can effectively remove particles that are too large or too small and improve the uniformity of the final product.
[0099] Please continue reading Figure 6 , placing the metal support in a suspension containing the nanoparticles and performing a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure.
[0100] In one embodiment of the present invention, the metal support is placed in a suspension containing the nanoparticles and subjected to a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure, comprising: performing a suspension preparation process on the nanoparticles to obtain a working suspension having preset electrophoretic properties; placing the metal support on a rotating bracket and immersing it in the working suspension, applying an electric field and performing acoustic wave excitation processes to obtain a preliminary deposition structure; performing real-time monitoring and parameter adjustment processes on the preliminary deposition structure to obtain a staged deposition structure with uniform thickness; performing surface activation and position adjustment processes on the staged deposition structure to obtain an intermediate deposition structure; repeating the above-mentioned electrophoretic deposition, monitoring and adjustment and surface treatment steps on the intermediate deposition structure to obtain a multilayer deposition structure; and performing a final surface treatment on the multilayer deposition structure to obtain an initial composite structure.
[0101] Specifically, first, nanoparticles with uniform particle size distribution are dispersed in deionized water, and an appropriate amount of electrolyte (such as sodium chloride or potassium chloride) is added to adjust the ionic strength. Subsequently, the suspension is treated with an ultrasonic disperser (power 500-1000W, frequency 20-40kHz) for 15-30 minutes to ensure that the nanoparticles are fully dispersed. Next, the surface charge of the nanoparticles is adjusted by controlling the pH value (for example, using a buffer solution to adjust the pH to a range of 7.0-8.5) and adding a surfactant (such as sodium dodecyl sulfate, concentration 0.1-0.5%) to obtain a working suspension with preset electrophoretic properties. This carefully prepared working suspension ensures that the nanoparticles have an appropriate migration speed and direction in the electric field, laying the foundation for the subsequent electrophoretic deposition process.
[0102] Next, the metal support is placed on a special rotating bracket that can rotate at a preset speed (such as 1-5rpm) during the deposition process to ensure uniform deposition. The rotating bracket with the metal support is immersed in the working suspension, and a DC electric field is applied to it using a precision power supply device, and the electric field strength is usually in the range of 50-200V / cm. At the same time, the suspension is acoustically excited using an acoustic wave generator with a power of 100-300W and a frequency of 20-60kHz. It should be noted that acoustic waves play multiple roles in the deposition process: first, acoustic waves can generate acoustic streaming, promote uniform mixing of the suspension, and prevent particle sedimentation; secondly, acoustic waves can destroy the electrical double layer around the particles and enhance the mobility of the particles; thirdly, acoustic waves can generate microbubbles at the particle-substrate interface, and the rupture of these microbubbles can enhance the bonding force between the particles and the substrate; finally, acoustic waves can also help particles overcome energy barriers and promote the deposition process through the action of acoustic pressure. By adjusting the frequency and intensity of the acoustic waves, these effects can be precisely controlled to optimize the deposition results.
[0103] The electric field drives the charged nanoparticles to move toward the surface of the metal support, while the acoustic excitation helps prevent particle agglomeration and promotes uniform deposition. This synergistic effect of the electric field and acoustic waves significantly improves the deposition efficiency and uniformity, and obtains the initial deposition structure.
[0104] In order to ensure accurate control of the deposition process, the preliminary deposition structure is monitored in real time and parameter adjustment is performed. The thickness of the deposited layer is measured in real time using a laser interferometer with a measurement accuracy of nanometers. At the same time, the dynamic changes of the deposition process are monitored using the current-time curve. Based on these real-time data, intelligent control algorithms (such as PID control or neural network algorithms) are used to dynamically adjust the electric field intensity, acoustic wave parameters, and rotation speed. For example, when it is detected that the thickness growth rate in a certain area is too fast, the local electric field intensity in the area can be reduced or the acoustic wave intensity can be increased to balance the deposition. Through this closed-loop control system, a staged deposition structure with uniform thickness is finally obtained, and the thickness variation can be controlled within ±5%.
[0105] Specifically, in order to accurately control the thickness and composition of each layer, the present invention adopts multiple real-time monitoring and feedback systems. First, the quartz crystal microbalance technology is used to monitor the deposition quality in real time, and its accuracy can reach the nanogram level. At the same time, the thickness and refractive index changes of the deposited layer are monitored in situ by using an ellipsometry spectrometer, and sub-nanometer thickness control can be achieved. In addition, by adjusting the ratio of different types of nanoparticles in the suspension, the composition of the deposited layer can be accurately controlled. For example, the ratio of PEEK and hydroxyapatite nanoparticles can be gradually changed during the deposition process to form a composite layer with a gradient structure. In order to ensure the uniformity of deposition, a multi-point laser interferometer is used to simultaneously monitor the deposition thickness at multiple locations, and the local electric field intensity and acoustic field distribution are adjusted in real time by a computer algorithm. In addition, by adjusting the pulse frequency and duty cycle of the electric field, the deposition rate of the nanoparticles can be finely controlled. For example, when forming an interface transition layer, a low-frequency pulse (such as 1-10Hz) can be used to promote the slow and orderly arrangement of the particles; and when forming the main structure, a high-frequency pulse (such as 100-1000Hz) can be used to improve the deposition efficiency. Through these advanced control strategies, the thickness of each layer can be controlled within an accuracy range of ±5nm, while achieving continuous and controllable changes in the composition of the deposited layers.
[0106] Surface activation and position adjustment of the staged deposition structure is a key step to ensure the stability of the multilayer deposition structure. First, the surface of the deposited layer is activated using low-power (50-100W) oxygen plasma for 30-60 seconds, which not only cleans the surface but also increases the surface energy, which is conducive to the adhesion of the next layer. Subsequently, the metal support is adjusted on the rotating bracket, such as changing the tilt angle or rotation direction, to ensure that the next stage of deposition can cover the weak areas that may have existed before. This surface activation and position adjustment treatment significantly improves the bonding strength and uniformity of the multilayer structure, resulting in an intermediate deposition structure with excellent performance.
[0107] The steps of electrophoretic deposition, monitoring and adjustment, and surface treatment are repeated for the intermediate deposition structure, and a new deposition layer is formed each time it is repeated. The preparation of functional gradient materials can be achieved by precisely controlling the thickness and properties of each layer. For example, different mechanical properties or biological activities can be achieved at different levels by adjusting the type and concentration of nanoparticles in the suspension. This multilayer deposition structure not only improves the overall mechanical properties, but also enables the spatial distribution of specific functions such as antibacterial and cell growth promotion.
[0108] Finally, the multilayer deposited structure is subjected to final surface treatment to obtain the initial composite structure. This step may include deep surface modification using high-power (200-300W) argon plasma for 3-5 minutes to enhance the biocompatibility of the surface. Subsequently, precise laser micromachining technology can be used to create specific microstructures on the surface, such as microgrooves or porous structures, to promote cell attachment and tissue growth. Finally, ultrasonic cleaning and vacuum drying are used to remove impurities that may remain on the surface to obtain a clean initial composite structure.
[0109] In one embodiment of the present invention, the real-time monitoring and parameter adjustment processing of the preliminary deposition structure to obtain a staged deposition structure with uniform thickness includes: performing multi-dimensional measurement and analysis processing on the preliminary deposition structure to obtain deposition layer characteristic data; performing coupling optimization processing on the electric field and the acoustic field according to the deposition layer characteristic data to obtain an electro-acoustic composite field; performing spatiotemporal modulation processing on the electro-acoustic composite field to obtain a dynamic deposition field; performing multi-scale simulation processing on the nanoparticle deposition process according to the dynamic deposition field to obtain a deposition parameter prediction model; performing machine learning training processing on the deposition parameter prediction model to obtain an intelligent deposition control model; performing real-time adjustment and optimization processing on the deposition parameters according to the intelligent deposition control model to obtain dynamically optimized deposition parameters; and performing closed-loop control deposition processing on the preliminary deposition structure using the dynamically optimized deposition parameters to obtain a staged deposition structure with uniform thickness.
[0110] Specifically, first, a high-precision white light interferometer is used to perform a three-dimensional profile scan of the surface of the deposited layer, with a resolution of up to 1nm and a scanning range of 10mm×10mm. At the same time, an X-ray diffractometer is used to perform structural analysis on the deposited layer to obtain crystal structure and phase composition information. In addition, an atomic force microscope is used to test the nanoscale morphology and mechanical properties of the surface of the deposited layer, with a probe scanning range of 100μm×100μm. These multi-dimensional measurement data are comprehensively analyzed and processed to obtain comprehensive deposited layer characteristic data including deposited layer thickness distribution, surface roughness, crystal structure, mechanical properties, etc.
[0111] According to the obtained sediment layer characteristic data, the electric field and the acoustic field are coupled and optimized. Using finite element analysis software, a three-dimensional model of the electric field and the acoustic field is established, and the sediment layer characteristic data is input into the model as boundary conditions. The spatial distribution of the electric field and the acoustic field is optimized by adjusting the electrode shape, the position of the acoustic generator, and the power distribution. For example, the local electric field strength is enhanced in areas with thin sediment layers, and the acoustic field distribution is adjusted to prevent particle agglomeration. Through the iterative optimization algorithm, the electric-acoustic composite field is finally obtained, which can provide the optimal combination of electric and acoustic fields for different areas of the sediment layer.
[0112] The electroacoustic composite field is subjected to spatiotemporal modulation to obtain a dynamic deposition field. This step uses pulse modulation technology to precisely control the electric field and the acoustic field in time and space. For example, the pulse frequency of the electric field can be set to 1-10kHz, the duty cycle can be 50-80%, and the modulation frequency of the acoustic field can be set to 20-50kHz. By changing the pulse parameters in different areas, dynamic regulation of the deposition field is achieved. This spatiotemporal modulation can not only precisely control the motion trajectory of the nanoparticles, but also effectively prevent local overheating and bubble generation, thereby obtaining a more uniform and stable dynamic deposition field.
[0113] The nanoparticle deposition process is simulated at multiple scales based on the dynamic deposition field. This step combines molecular dynamics simulation and continuum theory to establish a multiscale model from nanoscale to macroscale. At the nanoscale, the movement and interaction of individual particles in the electroacoustic field are simulated; at the micrometer scale, the collective behavior of a group of particles is simulated; at the macroscale, the growth process of the entire deposition layer is simulated. This multiscale simulation takes into account factors such as van der Waals forces, electrostatic forces, and fluid dynamic interactions between particles, and can accurately predict deposition behavior under different deposition parameters, thereby obtaining a comprehensive deposition parameter prediction model.
[0114] The deposition parameter prediction model is trained by machine learning to obtain an intelligent deposition control model. This step uses a deep neural network algorithm to input a large amount of simulation data and experimental data into the network for training. The structure of the neural network contains multiple convolutional layers and fully connected layers, which can capture nonlinear relationships and complex patterns in the deposition process. The network parameters are continuously optimized through the back propagation algorithm, and finally an intelligent deposition control model that can accurately predict the deposition results is obtained. This model can not only predict the deposition results based on the input deposition parameters, but also reversely derive the parameter combination required to achieve a specific deposition target.
[0115] The deposition parameters are adjusted and optimized in real time according to the intelligent deposition control model. During the deposition process, the real-time monitoring system continuously collects data such as the thickness and uniformity of the deposition layer, and inputs these data into the intelligent deposition control model. Based on these real-time data, the model quickly calculates the optimal combination of deposition parameters, including electric field strength, acoustic field strength, pulse frequency, etc. These optimized parameters are used to adjust the deposition equipment in real time through the feedback control system to obtain dynamically optimized deposition parameters. This real-time optimization process can quickly respond to changes in the deposition process and ensure continuous optimization of deposition quality.
[0116] Finally, the preliminary deposition structure is subjected to closed-loop controlled deposition processing using dynamically optimized deposition parameters. This step tightly integrates the intelligent control system with the deposition equipment to form a complete closed-loop control system. The system continuously adjusts deposition parameters such as electric field strength, acoustic field strength, rotation speed, etc. based on real-time monitoring data and predictions from intelligent models. For example, when a decrease in the deposition rate in a certain area is detected, the system automatically increases the electric field strength in that area or adjusts the acoustic field distribution. This closed-loop control ensures the high stability and controllability of the deposition process, and ultimately obtains a staged deposition structure with uniform thickness, the thickness uniformity of which can be controlled within ±2%.
[0117] Please continue reading Figure 6 , performing femtosecond laser microstructuring processing on the surface of the initial composite structure to obtain a composite structure with a preset surface microstructure.
[0118] Specifically, the process of femtosecond laser microstructuring the surface of the initial composite structure begins with the use of a high-precision femtosecond laser system. The system is usually equipped with a titanium sapphire laser with a wavelength of 800nm and a pulse width of 100fs, a pulse energy of up to 1-10mJ, and a repetition rate of 1-10kHz. First, the initial composite structure is fixed on a precise three-axis mobile platform with a positioning accuracy of up to 0.1μm to ensure high accuracy during the processing. Next, computer-aided design software is used to pre-design the required surface microstructure patterns, which may include microgrooves, micropore arrays, or specific biomimetic structures. For example, in order to promote the attachment and growth of bone cells, a micromorphology similar to the trabecular structure can be designed.
[0119] Subsequently, the designed pattern is imported into the laser processing control system, and the system automatically converts the pattern into a laser scanning path. In the actual processing process, the femtosecond laser beam is focused onto the surface of the composite structure through a focusing lens with a high numerical aperture, and the focus point diameter can be as small as 1μm. Due to the ultra-short pulse characteristics of the femtosecond laser, it can generate extremely high instantaneous power density on the surface of the material, achieving - W / This high energy density can cause nonlinear absorption of the material in a very short time, resulting in rapid gasification of the material without significant thermal effects. This "cold processing" process greatly reduces the heat-affected zone and ensures processing accuracy and surface quality.
[0120] By precisely controlling the laser power, scanning speed, and number of repetitions, a preset microstructure can be precisely etched on the surface of the composite structure. For example, by adjusting the laser power between 50-200mW and the scanning speed between 0.1-10mm / s, a microgroove structure with a depth of 1-100μm and a width of 1-50μm can be obtained. In addition, by changing the laser scanning mode, such as using spiral scanning or raster scanning, microstructures of different shapes and arrangements can be manufactured, such as circular microhole arrays or grid-like microstructures.
[0121] The advantages of this femtosecond laser microstructuring method are its high precision, high flexibility and low thermal impact. It can create precisely controlled three-dimensional microstructures on the surface of the composite structure, which can not only optimize the interfacial interaction between the implant and the biological tissue, but also regulate the adhesion, proliferation and differentiation behavior of cells. For example, by creating microgrooves of specific size and arrangement on the surface, bone cells can be guided to grow in a specific direction, thereby promoting the bone integration process. In addition, this method can also create multi-scale hierarchical structures on the surface to simulate the micromorphology of natural bone tissue, further enhancing the biocompatibility and bone integration ability of the implant.
[0122] Through this precise femtosecond laser microstructuring, the initial composite structure is given a preset surface microstructure, resulting in a composite structure with optimized surface properties. This structure not only has a precisely controlled surface morphology, but also retains the excellent properties of the matrix material, laying a solid foundation for subsequent biological evaluation and clinical application.
[0123] Please continue reading Figure 6 , a multi-stage gradient heat treatment is performed on the composite structure with a preset surface microstructure, and a plasma chemical vapor deposition treatment is performed on the composite structure after the heat treatment to obtain an implant prosthesis with a preset shape.
[0124] In one embodiment of the present invention, the multi-stage gradient heat treatment is performed on the composite structure with a preset surface microstructure, and the composite structure after the heat treatment is subjected to plasma chemical vapor deposition treatment to obtain an implant prosthesis with a preset shape, including: performing a first-stage low-temperature heat treatment on the composite structure with a preset surface microstructure, the treatment temperature is 30°C below the glass transition temperature of the polymer material, and the treatment lasts for 4 hours to obtain a composite structure with initial stress release; performing a second-stage medium-temperature heat treatment on the composite structure with initial stress release, the treatment temperature is 30°C above the glass transition temperature of the polymer material, and the treatment lasts for 6 hours to obtain a composite structure with improved crystallinity; performing a third-stage high-temperature heat treatment on the composite structure with improved crystallinity, the treatment temperature is above the melting point of the polymer material. The composite structure is subjected to a temperature-controlled cooling process at a rate of 1°C / minute until room temperature, thereby obtaining a composite structure that has undergone heat treatment. The composite structure that has undergone heat treatment is subjected to an argon plasma activation process at a plasma power of 100W and a treatment time of 10 minutes, thereby obtaining a surface-activated composite structure. The surface-activated composite structure is subjected to a chemical vapor deposition process at a deposition material of dimethylsiloxane at a deposition temperature of 150°C and a deposition time of 30 minutes, thereby obtaining a surface-modified composite structure. The surface-modified composite structure is subjected to a nitrogen plasma post-treatment at a plasma power of 50W and a treatment time of 5 minutes, thereby obtaining an implant prosthesis with a preset shape.
[0125] Specifically, taking polyetheretherketone (PEEK) as an example, its glass transition temperature is about 143°C, so the treatment temperature in the first stage is set to 113°C. The composite structure is placed in a vacuum heat treatment furnace with precision temperature control, slowly heated to the target temperature under a nitrogen protective atmosphere, and maintained for 4 hours. The temperature below the glass transition temperature is selected to release internal stress without causing significant softening of the material. This temperature is sufficient to allow the molecular chains to gain a certain degree of activity, but not enough to cause large-scale molecular rearrangement. Through this step, the molecular chains of the material have gained a certain degree of activity, but have not yet reached the level of significant rearrangement, thereby obtaining a composite structure with initial stress release.
[0126] Next, the composite structure with initial stress release is subjected to the second stage of medium-temperature heat treatment. The temperature is raised to 173°C, which is 30°C above the glass transition temperature of PEEK, and lasts for 6 hours. The temperature above the glass transition temperature is selected to promote the movement and rearrangement of the molecular chains and improve the crystallinity of the material. This temperature puts the polymer in a rubbery state, which is conducive to the crystallization process. This stage of treatment is crucial to improving the crystallinity of the material, because a higher degree of crystallinity usually means better mechanical properties and chemical stability. After the treatment, a composite structure with improved crystallinity is obtained, and its crystallinity may be increased from the initial 30% to 40-50%.
[0127] The third stage of high temperature heat treatment further raises the temperature to 330°C, which is 10°C below the melting point of PEEK (about 343°C). The temperature close to but below the melting point is chosen to maximize the activity of the molecular chains without causing the material to completely melt. This is conducive to the strengthening of interfacial bonding and the elimination of any residual stress. Treated at this temperature close to the melting point for 2 hours, at such a high temperature, the polymer chain segments have extremely high activity and can better penetrate and entangle with the microstructure of the metal surface, thereby obtaining a composite structure with enhanced interfacial bonding. This step significantly improves the overall strength and durability of the composite material.
[0128] The last step of heat treatment is program-controlled cooling. A slow cooling rate of 1°C / minute is used to ensure the minimization of internal stress in the material and the stability of the crystalline structure. This precisely controlled cooling process is essential to maintain the internal structure and performance of the material, and ultimately obtain a composite structure that has been heat treated.
[0129] Subsequently, the heat-treated composite structure was activated by argon plasma. High-purity argon gas was introduced into the low-pressure chamber, and 100W of radio frequency power was applied to generate a stable plasma. The composite structure was exposed to the plasma for 10 minutes. This process not only cleaned the surface, but also generated a large number of active groups on the surface, providing a basis for subsequent chemical modification, thereby obtaining a surface-activated composite structure.
[0130] Next, the surface activated composite structure was treated with chemical vapor deposition. Dimethylsiloxane was selected as the precursor and the deposition was carried out at a temperature of 150°C for 30 minutes. This step formed a uniform silicone coating on the surface of the composite structure, which not only improved the hydrophobicity of the surface, but also enhanced the wear resistance and biocompatibility. By precisely controlling the deposition parameters, high-quality surface modified composite structures with a thickness in the range of 50-100nm can be obtained.
[0131] Finally, the surface-modified composite structure was post-treated with nitrogen plasma. A nitrogen plasma with a lower power (50W) was used for 5 minutes. The purpose of this step is to further improve the surface properties, such as introducing nitrogen-containing functional groups to enhance the hydrophilicity and bioactivity of the surface. Through this series of carefully designed heat treatment and surface modification steps, an implant prosthesis with a preset shape and optimized surface properties is finally obtained.
[0132] This multi-stage heat treatment combined with surface modification method has multiple advantages. First, the staged heat treatment process allows precise control of the internal structure of the material, from stress release to crystallinity enhancement to interface strengthening, each step specifically optimizes the specific properties of the material. Second, the slow cooling process ensures the stability of the internal structure of the material and reduces the deformation or cracking problems that may occur in subsequent use. Third, the surface modification method combining plasma treatment and chemical vapor deposition not only improves the surface properties of the material, but also provides the possibility for further biofunctionalization. Finally, each step of the entire process is carefully designed and optimized to ensure that the final product has excellent mechanical properties, chemical stability and biocompatibility, which is crucial for the long-term use of implant prostheses and patient safety.
[0133] It is worth noting that compared with traditional mold production solutions, the solution of the present invention exhibits significant advantages in many aspects. First, this manufacturing method based on selective laser melting and electrophoretic deposition has a higher degree of design freedom and can easily achieve complex internal structures and fine surface features, which are often difficult to achieve or too costly in traditional mold production. Secondly, this solution allows precise control of the composition and structure of the material at the microscale. Through multi-stage electrophoretic deposition and heat treatment processes, gradient changes in material properties can be achieved, thereby better simulating the structure and mechanical properties of natural bone tissue. In addition, this method has a higher material utilization rate and reduces material waste during processing.
[0134] More importantly, the production process of this solution has higher flexibility and customizability. By adjusting the deposition parameters, heat treatment conditions and surface treatment methods, the performance and shape of the product can be quickly adjusted according to the individual needs of different patients, achieving true personalized customization. This flexibility is difficult to achieve in traditional mold production. In addition, this solution integrates advanced real-time monitoring and intelligent control systems, which can make real-time adjustments and optimizations during the production process to ensure the consistency and reliability of product quality.
[0135] In terms of biocompatibility, this solution can better optimize the interaction between implants and human tissues by precisely controlling material composition and surface microstructure. For example, through femtosecond laser microstructuring and chemical vapor deposition, specific structures that promote cell attachment and tissue growth can be created on the implant surface, which is difficult to achieve in traditional mold production.
[0136] Finally, the production process of this solution is more environmentally friendly. It reduces the waste generated during mold manufacturing and replacement. At the same time, due to the use of technologies such as supercritical fluid-assisted spraying, the use of organic solvents is greatly reduced, reducing the risk of environmental pollution. In general, this innovative manufacturing method not only improves the performance and quality of the product, but also enhances the flexibility and environmental friendliness of the production process, opening up a new path for the future development of implant prostheses.
[0137] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing an implant prosthesis, wherein the method is used to prepare an implant prosthesis, and is characterized in that: The implant prosthesis comprises: A metal support (1), the metal support (1) comprising an annular wall (11), the material of the annular wall (11) being a biocompatible metal or an alloy thereof, the annular wall (11) being provided with a mechanical connection structure (12), the mechanical connection structure (12) comprising a first through hole (121) penetrating the annular wall (11) and / or a groove (122) recessed on the peripheral wall of the annular wall (11); An outer body (2), the outer body (2) comprising a spherical portion (21), a conical portion (22) and a solidified portion (23), the spherical portion (21) being connected to the outer peripheral wall of the annular wall (11) and being used for implanting the acetabulum (100), the conical portion (22) being connected to the inner peripheral wall of the annular wall (11) and forming a conical groove (221) for connecting with a femoral stem (200), the solidified portion (23) being arranged in the mechanical connection structure (12), the spherical portion (21), the conical portion (22) and the solidified portion (23) being integrally formed, and the materials of the spherical portion (21), the conical portion (22) and the solidified portion (23) are all biocompatible polymer materials; The preparation method of the implant prosthesis comprises: Providing a metal support with a preset geometry and surface properties; The biocompatible polymer material is subjected to supercritical fluid-assisted spray treatment, and the particles obtained after the treatment are electrostatically collected and characterized to obtain nanoparticles with uniform particle size distribution; Placing the metal support in a suspension containing the nanoparticles and performing a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure; Performing femtosecond laser microstructuring on the surface of the initial composite structure to obtain a composite structure having a preset surface microstructure; A multi-stage gradient heat treatment is performed on a composite structure with a preset surface microstructure, and a plasma chemical vapor deposition treatment is performed on the composite structure after the heat treatment to obtain an implant prosthesis with a preset shape.
2. The method for preparing an implant prosthesis according to claim 1, characterized in that: The preparation process of the metal support with a preset geometric structure and surface characteristics includes: Selective laser melting of biocompatible metal powder was performed to obtain a metal support prototype; Performing hot isostatic pressing on the metal support prototype to obtain a densified metal support; Performing surface roughening treatment on the densified metal support to obtain a metal support with a microscopic rough structure; Performing X-ray computed tomography on the metal support having the microscopic rough structure to obtain three-dimensional structural data of the metal support; Performing surface microstructure modification on the metal support according to the three-dimensional structure data to obtain a metal support with a preset surface morphology; The metal support member with a preset surface morphology is subjected to plasma surface activation treatment to obtain a metal support member with a preset geometric structure and surface characteristics.
3. The method for preparing an implant prosthesis according to claim 1, characterized in that: The method comprises: subjecting the biocompatible polymer material to supercritical fluid-assisted spray treatment, and electrostatically collecting and characterizing the particles obtained after the treatment to obtain nanoparticles with uniform particle size distribution, comprising: The biocompatible polymer material and supercritical carbon dioxide are mixed under high pressure to obtain a uniform solution; Performing high-pressure spraying on the uniform solution to obtain preliminarily formed nanoparticles; treating the initially formed nanoparticles with an ultrasonic field to obtain nanoparticles with improved dispersion; Performing electrostatic field collection treatment on the nanoparticles with improved dispersion to obtain a preliminary collected nanoparticle sample; Performing dynamic light scattering analysis on the initially collected nanoparticle samples to obtain particle size distribution data; The nanoparticle sample is centrifuged and classified according to the particle size distribution data to obtain nanoparticles with uniform particle size distribution.
4. The method for preparing an implant prosthesis according to claim 1, characterized in that: Placing the metal support in a suspension containing the nanoparticles and performing a multi-stage acoustic-assisted electrophoretic deposition process to obtain an initial composite structure comprises: Performing a suspension preparation process on the nanoparticles to obtain a working suspension having a preset electrophoretic property; Placing the metal support on a rotating bracket and immersing the metal support in the working suspension, applying an electric field and performing acoustic wave excitation treatment on the metal support to obtain a preliminary deposition structure; Performing real-time monitoring and parameter adjustment processing on the preliminary deposition structure to obtain a staged deposition structure with uniform thickness; Performing surface activation and position adjustment treatment on the staged deposition structure to obtain an intermediate deposition structure; Repeating the above-mentioned electrophoretic deposition, monitoring and adjustment, and surface treatment steps on the intermediate deposition structure to obtain a multilayer deposition structure; The multilayer deposition structure is subjected to final surface treatment to obtain an initial composite structure.
5. The method for preparing an implant prosthesis according to claim 4, characterized in that: The real-time monitoring and parameter adjustment process of the preliminary deposition structure to obtain a staged deposition structure with uniform thickness includes: Conduct multi-dimensional measurement and analysis of the preliminary sedimentary structure to obtain sedimentary layer characteristic data; According to the characteristic data of the sediment layer, the electric field and the acoustic field are coupled and optimized to obtain the electric-acoustic composite field; Performing spatiotemporal modulation processing on the electro-acoustic composite field to obtain a dynamic deposition field; Performing multi-scale simulation processing on the nanoparticle deposition process according to the dynamic deposition field to obtain a deposition parameter prediction model; Performing machine learning training on the deposition parameter prediction model to obtain an intelligent deposition control model; According to the intelligent deposition control model, the deposition parameters are adjusted and optimized in real time to obtain dynamically optimized deposition parameters; The dynamically optimized deposition parameters are used to perform closed-loop controlled deposition processing on the preliminary deposition structure to obtain a staged deposition structure with uniform thickness.
6. The method for preparing an implant prosthesis according to claim 1, characterized in that: The mechanical connection structure (12) comprises the first via hole (121); There are a plurality of first via holes (121), and the plurality of first via holes (121) are spaced apart in the circumferential direction of the annular wall (11); there are a plurality of solidifying portions (23), and the number of the plurality of solidifying portions (23) is the same as the number of the plurality of first via holes (121) and corresponds one to one; the solidifying portions (23) are arranged to fill the corresponding first via holes (121).
7. The method for preparing an implant prosthesis according to claim 1, characterized in that: The mechanical connection structure (12) comprises a slot body (122); There are a plurality of the groove bodies (122), and the plurality of the groove bodies (122) are all arranged on the outer peripheral wall of the annular wall (11) and are spaced apart in the circumferential direction of the annular wall (11). There are a plurality of the solidifying parts (23), and the number of the plurality of the solidifying parts (23) is the same as the number of the plurality of the groove bodies (122) and corresponds one to one. The solidifying parts (23) are arranged to fill the corresponding groove bodies (122).
8. The method for preparing an implant prosthesis according to claim 1, characterized in that: The metal support (1) further comprises a spherical cap wall (13), wherein the spherical cap wall (13) is connected to the end of the annular wall (11) away from the notch of the conical groove (221) and protrudes in a direction away from the notch of the conical groove (221).
9. The method for preparing an implant prosthesis according to claim 8, characterized in that: The spherical cap wall (13) is penetrated by a second through hole (131), and the outer body (2) includes a connecting portion (24), and the connecting portion (24) is arranged to fill the second through hole (131). The connecting portion (24) is integrally formed with the spherical portion (21) and the conical portion (22), and the material of the connecting portion (24) is a biocompatible polymer material.
Citation Information
Patent Citations
Total hip surface replacement implant
CN105030376A
Porous metal and PEEK composite implanted joint prosthesis and preparation method
CN112274299A